PENGARUH PEMBERIAN KOMBINASI BIOCHAR TANKOS DAN PUKAN SAPI TERHADAP EFESIENSI SERAPAN N, P, K, DAN HASIL TANAMAN CABAI BESAR DI TANAH ALLUVIAL - Borneo, Ginelar Noto; Vitri Indrawati, Urai Suci Yulies; Junaidi, Junaidi (Fakultas Pertanian, Universitas Janabadra, 2024)
The large chili plant (Capsicum annum L.) is one type of important horticultural plant that is cultivated commercially. It has quite complete nutritional content and also has high economic value. This research was carried out for 6 months, in the experimental field of the Faculty of Agriculture, Tanjungpura University, Kota. Pontianak, West Kalimantan Province starting from preparing the planting media until the plants reach the maximum generative phase. Presentation of analytical data was obtained from the Chemistry Laboratory, Physics Laboratory, Tanjung Pura University. This research used a factorial Completely Randomized Design (CRD) method consisting of 2 factors, namely tankos biochar and cow manure. 3 levels of treatment. Each factor was repeated 3 times and in 3 pots without treatment, so that 30 polybags were obtained. Observation variables in this research included dry weight (g), N uptake (mg), P uptake (mg), K uptake ( mg), Fruit Weight (g), Fertilization Efficiency, The results of the research show that the real influence is Plant Dry Weight 17.306%, and fruit weight 798.64%, N, P, K uptake efficiency, the highest uptake value is K B3P3 31 .46%. Keywords : big chili, alluvial, biochar, NPK uptake, efficiency